DOCUMENTING A RETURN TO HISTORICAL JAZZ THROUGH MUSICAL RESEARCH AND CREATION. - Weybrecht, Thomas (East Carolina University, 2019)
In 1985, Bill Hubbard, a prolific big band jazz arranger, died and left behind a horde of musical charts, as well as musical protégés in sons Glenn and Curt Hubbard and their friend Matt Vance. Much of the music Hubbard arranged had never seen the light of day since being written, and even less was heard within the context of a jazz ensemble. In 2017, Vance and the Hubbard brothers solidified plans to assemble a team of musicians to play and record a selection of Hubbard’s music for an album. The main recording session took place in June of 2018 in Jacksonville, Florida. Using footage from this recording session and compiled from archives, I produced a documentary entitled The Legacy Sessions. Production of the documentary had two purposes. Purpose No. 1 was to tell a story I believe was unique and worthy of telling, and was one I believed I could accurately convey through a video production. The history of the impact that Hubbard had on his contemporaries and successors is a powerful one, lush with family ties and memoirs of musical adventures. Through footage of the recording project and interviews with those involved, I combined visual and auditory content into a story that does justice to the Hubbard musical legacy. Two distinct themes are prevalent through the story: a subversion of the extinction of jazz music as popular music, and the importance of passing down experiences to preserve the Hubbard family’s rich musical history. Purpose No. 2 was to hone and utilize my video production skills by challenging myself to apply new and foreign editing techniques; employ a large array of cameras in the filming stage; dig deeper than I ever have into interviews and research to gather information about the story; and utilize proper journalistic strategy in producing an accurate and captivating rendition of the story of the Bill Hubbard Orchestra. The end result, then, is not only a piece of film which documents an interesting story, but also an exercise in video production that reflects my own learnings throughout my career, and especially during this project.
Keywords: jazz documentary, musical history